A study of the potential interactions between azapropazone and frusemide in man. - Williamson, P J (1984)
Ten healthy individuals received frusemide 40 mg orally for 7 days. Following a drug free period of 7 days they received azapropazone 600 mg twice daily for 7 days and then both treatments for a further 7 days. Sodium excretion fell from 141 +/- 16.8 mmol/day to 84.3 +/- 6.8 mmol/day (P less than 0.01) on initiation of azapropazone treatment. The natriuretic response to frusemide was unchanged by premedication with azapropazone. Urate excretion rose from 3.35 +/- 0.249 mmol/day to 4.98 +/- 0.365 mmol/day on initiation of azapropazone therapy but subsequently returned to baseline values. Plasma uric acid fell from 0.289 +/- 0.024 mmol/l to 0.167 +/- 0.0125 mmol/l (P less than 0.001) on azapropazone but rose to 0.186 +/- 0.0116 mmol/l (P less than 0.001) with the addition of frusemide. Azapropazone may cause sodium retention but after repeated administration frusemide still has a marked diuretic action. The hypouricaemic effect of azapropazone is only slightly antagonised by frusemide at the doses studied.